Inka human sacrifice and mountain worship strategies for empire unification - Besom, Thomas, 1960- (Albuquerque : University of New Mexico Press, 2013)
"In this study, Besom explores the ritual practices of human sacrifice and the worship of mountains, attested in both archaeological investigations and ethnohistorical sources, as tools in the establishment and preservation of political power within the Inka empire"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Incas -- Rites and ceremonies; Incas -- Religion; Incas -- Politics and government; Human sacrifice -- Andes Region; Andes Region -- Religious aspects; Mountains -- Religious aspects; Andes Region -- Antiquities; RELIGION / Ethnic & Tribal; Electronic books